2011
DOI: 10.1007/s00520-011-1160-6
|View full text |Cite
|
Sign up to set email alerts
|

EORTC QLQ-C15-PAL quality of life scores in patients with advanced cancer referred for palliative radiotherapy

Abstract: As the QLQ-C15-PAL provides detailed and often critical information regarding symptom burden, it may eventually be recognized as a universal core questionnaire to assess QOL in this patient population with advanced cancer while relieving the survey burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
33
1
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 20 publications
(23 reference statements)
3
33
1
5
Order By: Relevance
“…Two studies showed that higher KI correlate with better QLQ-C30 scales [37, 38]. This corresponds with our data.…”
Section: Discussionsupporting
confidence: 92%
“…Two studies showed that higher KI correlate with better QLQ-C30 scales [37, 38]. This corresponds with our data.…”
Section: Discussionsupporting
confidence: 92%
“…It points out that the majority of the elderly population aged 60 years old or more is composed of women (55.7%), due to the effects of differential mortality by gender. 22 It is significant to observe that even more recent research, carried out in developed countries with cancer patients, also highlighted the average age between 60 and 69 years old, [23][24] which only corroborates the data found in this study.…”
Section: Discussionsupporting
confidence: 77%
“…Although a few studies investigated the relationship between the PS and QOL in patients undergoing radiotherapy, few studies have examined changes in the PS before and after palliative radiotherapy [14] [15]. The results of this study showed an improvement in the QOL after irradiation, whereas there were no significant changes in the PS after palliative radiotherapy.…”
Section: Discussioncontrasting
confidence: 37%